PENGARUH PENAMBAHAN TEPUNG Spirulina platensis DALAM PAKAN TERHADAP PERTUMBUHAN DAN EFISIENSI PAKAN IKAN MAS KOKI (Carassius auratus) - Nuraini nazhiroh; mulyana mulyana; fia sri mumpuni (JURNAL MINA SAINS, 2019)
The research is aimed to know the supplementation effect of different concentration of Spirulina platensis fluor on artificial feed against the growth and feed efficiency of goldfish. The experimental research was carried out on September 2018 until April 2019 at The Fisheries Laboratory, Djuanda University, Bogor. The experimental research used completely randomized design with 4 treatments and each 3 replications. The treatments are K (Control, without supplementation of Spirulina platensis fluor), A (30 g of Spirulina platensis fluor + 1 kg  of artificial feed), B (60 g of Spirulina platensis fluor + 1 kg  of artificial feed), and C (90 g of Spirulina platensis fluor + 1 kg  of artificial feed). The total length growth, the weight growth, feed efficiency, and water quality (temperature, pH, dissolved oxygen, and NH3) had been evaluated.  The results of research showed there was  a significantly different between treatments for the growth and feed efficiency (P<0.05).  The best results were obtained in treatment B with an average total length growth of 2.19 cm, average weight growth of 1.51 g, and average feed efficiency of 30.26%. Water quality during the research are temperaure of 25.6-27.5oC, pH of 7.2-8.3,  DO of 6.2-7.1 mg/L, and NH3 of 0.01-0.30 mg/L.Key words : Goldfish, Spirulina platensis, growth, feed efficiency